2021
DOI: 10.1016/j.atmosres.2020.105264
|View full text |Cite
|
Sign up to set email alerts
|

Destinations frequently impacted by dust storms originating from southwest Iran

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…The mean surface dust concentration exhibited values ranging between 200 µg m −3 and 250 µg m −3 , while both parameters showed lower values during the beginning of the examined period, as well as in 2014 and 2016. Due to distinct seasonality of dust in SW Iran [64,80,140,141], the annual variability is mostly driven by the dust patterns in spring and summer, when dust activity highly maximizes. Karimi et al [142] also showed that 2008 and 2009 were the dustiest years from 2005 to 2015m and July was the dustiest month during that time frame [143].…”
Section: Satellite Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean surface dust concentration exhibited values ranging between 200 µg m −3 and 250 µg m −3 , while both parameters showed lower values during the beginning of the examined period, as well as in 2014 and 2016. Due to distinct seasonality of dust in SW Iran [64,80,140,141], the annual variability is mostly driven by the dust patterns in spring and summer, when dust activity highly maximizes. Karimi et al [142] also showed that 2008 and 2009 were the dustiest years from 2005 to 2015m and July was the dustiest month during that time frame [143].…”
Section: Satellite Observationsmentioning
confidence: 99%
“…The largest city in this region, Ahvaz, is among the five most polluted cities worldwide in terms of particulate matter below 10 µm (PM 10 ) concentrations due to high frequency of dust events, imposing deleterious effects on environment, agriculture, aviation, industrial activity, culture, and public health [74][75][76]. Major sources of dust that affect SW Iran include the Sahara Desert and deserts in Iraq, Saudi Arabia, and Kuwait [77][78][79][80]. Dried marshy regions between the Tigris and Euphrates rivers are the most effective dust-emitting sources impacting SW Iran [52,54,[81][82][83].…”
Section: Introductionmentioning
confidence: 99%
“…The results of Broomandi et al (2020) indicated that Horolazim area acts as a source in the region. The susceptibility of southern area of Horolazim wetland to turn into a persistent dust centers has been mentioned in other studies (Broomandi et al, 2017;Cao et al, 2015;Heidarian et al, 2018).…”
Section: Main Local Dust Sources Due To Land Use/cover Changementioning
confidence: 92%
“…The HYSPLIT model from NOAA is one of the most extensively used atmospheric transport and dispersion models to compute air parcel trajectories, as well as complex transport, dispersion, chemical transformation, and deposition simulations [ [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] ].…”
Section: Methodsmentioning
confidence: 99%